Adulto de 49 años con trastorno bipolar tipo II y trastorno por déficit de atención e hiperactividad (TDHA) - Márquez Benza, Karen (2016)
This research consists in the exploration of a unique case study of a male subject of 49 years of age, diagnosed with ADHD and bipolar disorder type II. This research allows to identify the ADHD and bipolar disorder type II symptomatology through the patient’s history via the anamnesis. It also describes the subject´s neuropsychological profile to verify his current cognitive performance. After revising the current symptomatology and the neuropsychological profile that were found, a pertinent intervention based on the results is proposed.